The dark side of transformational leadership a critical perspective - Tourish, Dennis (New York Routledge, 2013)
Most research into leadership has presented leaders as heroic, charismatic and transformational ?visionaries?. The leader, whether in business, politics or any other field, is the most important factor in determining whether organizations succeed or fail. Indeed, despite the fundamental mistakes which have, arguably, directly led to global economic recession, it is often still taken for granted that transformational leadership is a good thing, and that leaders should have much more power than followers to decide what needs to be done.
Includes bibliographical references and index
Keywords: Transformational leadership